2023
DOI: 10.1055/s-0043-57034
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Kallikrein as a Forgotten Clotting Factor

Abstract: For decades, it was considered that plasma kallikrein's (PKa) sole function within the coagulation cascade is the activation of factor (F)XII. Until recently, the two key known activators of FIX within the coagulation cascade were activated FXI(a) and the tissue factor–FVII(a) complex. Simultaneously, and using independent experimental approaches, three groups identified a new branch of the coagulation cascade, whereby PKa can directly activate FIX. These key studies identified that (1) FIX or FIXa can bind wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The second manuscript in this issue, by Kearney and colleagues, refocuses the spotlight on plasma kallikrein (PKa) and its additional role within the coagulation cascade in directly activating coagulation factor IX (FIX). 2 Three independent studies corroborate a classic canonical intrinsic pathway (FXII-FXI-FIX) and a noncanonical pathway (PKa-FIX). With the existence of PKa as a coagulation clotting factor established, the next step is the investigation of the products of its cleavage as it relates to the functioning of the body.…”
mentioning
confidence: 88%
“…The second manuscript in this issue, by Kearney and colleagues, refocuses the spotlight on plasma kallikrein (PKa) and its additional role within the coagulation cascade in directly activating coagulation factor IX (FIX). 2 Three independent studies corroborate a classic canonical intrinsic pathway (FXII-FXI-FIX) and a noncanonical pathway (PKa-FIX). With the existence of PKa as a coagulation clotting factor established, the next step is the investigation of the products of its cleavage as it relates to the functioning of the body.…”
mentioning
confidence: 88%
“…The common pathway, responsible for the formation of fibrin to occlude the vessel, is initiated by both the intrinsic and extrinsic pathways [11]. Following activation of factor X via either the intrinsic or extrinsic pathway, the inactive enzyme prothrombin is converted into the active enzyme thrombin by the enzyme prothrombinase.…”
Section: Common Routementioning
confidence: 99%
“…These include TF/FVIIa-mediated activation of FIX, TF/FVIIa/FXa-mediated activation of FVIII, thrombin-mediated activation of FXI, and PKa-mediated activation of FIX. 10 , 11 , 12 , 13 We previously reported that although TF/FVIIa-mediated activation of FIXa was readily apparent in mouse plasma, there was no evidence of thrombin-mediated activation of FXI. 14 Interestingly, however, more recently, we reported on a mouse whole blood (WB) TG assay that was sensitive to both TF/FVIIa-mediated activation of FIX and thrombin-mediated activation of FXI.…”
Section: Introductionmentioning
confidence: 99%
“…PK and FXI are products of an ancient gene duplication event, leading to the hypothesis that the 2 enzymes may share the ability to cleave and activate FIX. 13 , 16 , 17 Early studies demonstrated that PKa could indeed directly activate FIX in purified systems. 18 , 19 , 20 , 21 A series of more recent studies further demonstrated direct FIX activation by PKa in both purified and plasma-based systems.…”
Section: Introductionmentioning
confidence: 99%